Climate change and environmental social conflicts in intermediary cities of Latin America and the Caribbean - Novillo Rameix, Norha Nathalia (2018)
More than 50% of Latin America and Caribbean population lives in areas with a high risk of vulnerability to climate change. It is associated with several threats such as extreme rainfall, landslides, droughts, food shortages and health risks. Since 1990, the region has experienced sustained urban growth, especially in intermediate cities, where the informal residential area has doubled. Segregation has increased due to lack of access to land, which is why both variables (informality and segregation) should be considered when analyzing vulnerability to climate change in intermediate cities. On the other hand, in the field of urban studies, it is established that there is a close relationship between socio-environmental conflicts and the control of territories, especially due to changes in land use and the externalities related to it. Although the analyzed cases do not show a directly proportional relationship between socio-environmental conflict and climate change in intermediate cities, it is evident that changes in future climate conditions could exacerbate current scenarios.